Penerapan media pembelajaran papan keranjang pembelajaran IPAS kelas IV SD - Septia adelia putri; efryda savita anjarwati; Isna Rahmawati . (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research aims to determine the application of basket board learning media for science and science learning in class IV elementary schools. This type of research uses a qualitative descriptive method. The instrument used is documentation. The subjects of this research were 19 grade IV students at SD Negeri 1 Towangsan for the 2023/2024 academic year. The results of this research are that by using basket board media students understand the material provided better, create a pleasant learning atmosphere and make students more active in learning.